Challenges and Economic Feasibility of Betelvine Cultivation in Uttar Pradesh - Kumar, Ajay; Yadav, Sudheer Kumar; Jangid, Rakesh; Gupta, A. K.; Kumar, Amit; Kumar, Deepak; Shankar, Kripa (International Journal of Economic Plants, 2023)
Betel vine (Piper betel L.) is referred to as “Paan” in India. It is the most significant and profitable commercial crop and is cultivated as a significant cash crop due to its high benefit cost ratio (2.3). Fresh betel leaves found rich source of phyto-nutrients and vitamins viz., proteins, minerals, fibre, carbohydrates, vitamin A and vitamin B1. Uttar Pradesh region is favourable for better cultivation of betel vine. There are a few areas in Uttar Pradesh that are well-known for growing betel leaves, such as Bundelkhand, Varanasi, and Unnao. Betel vine farming is labour and capital intensive and best suited to small-scale farmers with a stable source of work and income. The main challenges associated with betel vine cultivation are lack of quality planting material, disease and pest infestation, lack of market, and natural calamities. Leaf rot, wilt, and leaf spot are the major diseases that significantly affect the quality and productivity of betel leaves. But due to its perishable nature and price fluctuations, this is one of the biggest marketing challenges faced by betel vine farmers. Establishing a market intelligence system to forecast prices in advance and simultaneously exploring the export market may be beneficial for realising a higher return on betel vine cultivation. Young farmers are excited to cultivate the betel vine and promote it as a cash crop for gainful employment in Uttar Pradesh. The Government of Uttar Pradesh has launched a scheme to promote the quality production of betel vine leaves.